The Borrelia burgdorferi Glycosaminoglycan Binding Protein Bgp in the B31 Strain Is Not Essential for Infectivity despite Facilitating Adherence and Tissue Colonization - Schlachter, Samantha (Infect Immun, 2018)
The Lyme disease-causing organism Borrelia burgdorferi is transmitted into the mammalian host by an infected-tick bite. Successful infection relies on the ability of this extracellular pathogen to persist and colonize different tissues. B. burgdorferi encodes a large number of adhesins that are able to interact with host ligands to facilitate adherence and tissue colonization. Multiple glycosaminoglycan binding proteins present in B. burgdorferi offer a degree of redundancy of function during infection, and this highlights the importance of glycosaminoglycans as host cell receptors for spirochete adherence. Of particular interest in this study is Borrelia glycosaminoglycan binding protein (Bgp), which binds to heparin-related glycosaminoglycans. The properties of a bgp transposon mutant and a trans-complemented derivative were compared to those of the wild-type B. burgdorferi in the in vitro binding assays and in infection studies using a C3H/HeJ mouse infection model. We determined that the loss of Bgp impairs spirochete adherence, infectivity, and tissue colonization, resulting in a reduction of inflammatory manifestations of Lyme disease. Although Bgp is not essential for infectivity, it is an important virulence factor of B. burgdorferi that allows adherence and tissue colonization and contributes to disease severity.